Benzodiazepines and central glycine receptors. - Curtis, D R (1976)
1 In cats, anaesthetized with pentobarbitone, intravenous diazepam (minimum dose 3.0 mg/kg) enhanced dorsal root potentials but did not significantly diminish the reduction by electrophoretic strychnine of the inhibitory action of electrophoretic glycine on dorsal horn interneurones. 2 In mice, intraperitoneal diazepam (2.5 mg/kg) had no appreciable effect on the potency of strychnine as a convulsant, although providing some protection against bicuculline. 3 These observations, together with the failure of chlordiazepoxide to either inhibit the firing of spinal interneurones or reduce antagonism between strychnine and glycine when administered locally, provide no support for the interaction between benzodiazepines and mammalian central glycine receptors which has been proposed on the basis of in vitro studies of strychnine binding.